Electrical feed drives in automation : basics, computation, dimensioning - Gross, Hans, ....-; Hamann, Jens, ....-; Wiegartner, Georg, ....- (Erlangen : Publicis-MCD, 2001)
This book provides a comprehensive introduction into the fundamental physics and basic technical principles of automatic control and drive technology. It pays particular attention to the design and dimensioning of electrical feed drives in automation technology. It helps engineers and technicians to put into practice the theoretical fundamentals of automatic control and drive technology for machines in the tool, glass and ceramics industries as well as in the woodworking and packaging industries. It also deals with the application of robots and other manipulators. The relationships between automatic control and mechanical engineering are described and explained, making the book also particularly useful for students of technical disciplines.
Keywords: Automatic control; Control theory; Motion control devices